Culture as a starting point to understand Latin America's political problems (Colección, 2017)
The international community, as a decentralised community of nations, implies certain harmonic coexistence among cultures. Talking about different cultures means considering diverse values that are reflected on that coexistence’s order. Almost all current conflicts that concern international experts are consequence of an unresolved relationship among cultures. This is also evident in Latin America.In this paper, two main issues are tackled, first the theoretic concept of cultural identity; and second, the identification of the different cultures that have met in the (sub)continent. In the first place, the Spanish and Portuguese with the indigenous expressions. Later, the Africans with the Anglo-Saxons, which did not prove to be a proper integration. Cultural emptiness is the current problem in Latin America. The original cultures have disappeared or are no longer relevant displaced by the Europeans, which did not worried about blending each other values in a new one. Only the Jesuits in their Missions tried to accomplish this goal but, after a century and a half, left the idea.
Keywords: Political Culture; Culture; Colonization